Preparation and polymerization of isopimaric acid derivatives. Issue 31 (12th April 2019) - Lu, Yanju; Zhao, Zhendong; Bi, Liangwu; Chen, Yuxiang; Gu, Yan; Wang, Jing
ABSTRACT: Isopimaric acid is a typical rosin compound and can account for 30% of the total mass of slash pine rosin. The molecular structure of isopimaric acid derivatives features an unsaturated double bond at the C13 position, opening up the possibility of their industrial polymerization. In this study, isopimaric acid (95.4%), methyl isopimarate (99.5%), and allyl isopimarate (95.1%) were prepared as highly pure monomers. New experimental results are presented and mechanisms based on the investigation of free‐radical polymerization under UV irradiation are proposed. New rosin monomers for potential value‐added utilization of woody biomass are also identified. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47817. Abstract :